EFFECT OF BIO-FERTILIZER AND PHOSPHORUS LEVELS ON YIELD AND YIELD COMPONENTS OF CHICK PEA UNDER RAIN FED CONDITION - ZAKHOYI, HOGIR SALIM MOHAMMED; HUSSAIN, MOHAMMED ALI; OMER, OMER ANWAR (Journal of Duhok University, 2021)
A field experiment was carried out during the spring 2020 to evaluate the effect of phosphorus levels and bio-fertilizer on growth and yield of local variety of chick pea. It was conducted at the farm the College of the Agricultural Engineering Sciences, the experimental units laid out in Factorial arrangement using Randomize Complete Block Design with three replications, using three levels of phosphorus (0, 20 and 30 Kg P2O5 ha-1) and three levels of bio-fertilizer (0, 4 and 6 Kg ha-1). The results indicated that the effect of phosphorus, bio-fertilizer and interaction between them exhibited significant effect on all studied characters. The effect of interaction showed highest values for the pods height (36.06cm), percent of phosphorus in seed was (0.446), plant height (59.428cm), number of pods plant-1 (64.16), seeds weight (5.583 ton ha-1), number of primary and secondary branches plant-1(4 and 15.50) respectively, number of nodules were (31.978) and the weight of nodules were (0.369g) obtained at the interaction effect of fertilizer levels 30 Kg P2O5 ha-1 and 6 Kg ha-1 bio-fertilizer in comparing with other interaction combinations and control. Also the results indicated that the percentage of the element efficiency under different phosphorus and bio-fertilizer levels, the efficiency of the element increased with initial increasing in phosphorus rate and recorded 70.72% comparing with control